Karakteristik Hidrogeokimia Air Menggunakan Analisis Perbandingan Diagram Piper di Daerah Aliran Sungai Cikapundung - Nafisah, Lanny Amatun (Institut Teknologi Sains Bandung, 2024)
Cikapundung River is one of the important rivers that supply water to Bandung City. However, in the process of flowing, the water has received various kinds of pollutants. Poor water quality causes the physical and chemical parameters of the water to change. This study aims to determine the elemental content contained in river water. Water quality testing was conducted using inductively coupled plasma mass spectromertry (ICP-MS). Based on the analysis of the Piper Diagram, the type of water obtained is more dominant in the calcium-bicarbonate type (Ca - HCO3). This indicates that the water found is either shallow groundwater or spring water. The type of bicarbonate (HCO3) water indicated comes from the weathering of rock material and minerals close to the surface. The presence of calcium (Ca) contained in the groundwater may come from the presence of rocks containing carbonate minerals (CO3), besides that the water is indicated to have interacted with rocks containing silicate minerals that can affect the element Ca. Both diagrammatic approaches provide information about the evolutionary process that occurs in the Cikapundung River Sub-watershed. Thus, it is known that the water in the Cikapundung Sub-watershed has undergone ion exchange which causes the water quality to become unfit due to the presence of pollutant levels obtained from industrial and household waste disposal exceeding the standard class of River Water Quality Standard according to Government Regulation No. 22 of 2021 concerning Implementation of Environmental Protection and Management